Continuous approximation and GIS-enhanced design optimization of feeder bus networks along rail corridors - Jiahe Liu; Rui Song (PLoS ONE, 2025)
As urbanization accelerates, urban public transportation systems are tasked with meeting the growing demand for travel. According to statistics, the regional rail transit network currently handles 60% of the passenger volume for trips originating from around the stations, and this is projected to increase by over 20% within the next decade. However, the current feeder bus services suffer from insufficient coverage, leading to inconvenience for passengers and impacting the overall efficiency of the transportation system. To enhance the public transit service coverage along a rail transit corridor, this study designs feeder bus services to connect the rail stations. A theoretical trunk-feeder transit design problem is firstly solved to furnish the initial feeder bus line designs. The objective is to minimize total generalized system cost with respect to the density of feeder bus routes and their service frequencies. The idealized design of the optimal bus route density function is then discretized into specific locations and fine-tuned with Geographic Information System (GIS) tool. Considering local conditions like road network and demographic information, a four-step adjustment strategy is proposed to furnish the implementation-ready design of feeder bus services. Numerical results show the final design renders at least 3.5% saving in total system cost. This study illustrates how the state-of-the-art theories of transit design can be applied into practice and highlights the connection between theoretical studies and practical application.